2020
DOI: 10.1186/s12879-019-4748-y
|View full text |Cite
|
Sign up to set email alerts
|

High index of suspicion for brucellosis in a highly cosmopolitan city in southern China

Abstract: Background: Brucellosis is one of the most widespread zoonosis in the world. In China, 90% of human brucellosis occurs in six northern agricultural provinces. However, there is a recent increase in the trend of human brucellosis in southern provinces with limited cases reported in the literature. Our study aims to describe the clinical features and epidemiology of brucellosis in a tertiary hospital in southern China. Methods: A retrospective case series of brucellosis was conducted between January 1, 2014 and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 18 publications
(20 reference statements)
1
2
0
Order By: Relevance
“…However, our findings align with those from Pakistan, where Brucella-related EO was reported in 16.7% (n = 23) of 138 EO cases [26]. Similarly, a study in China revealed that 30.7% of patients with confirmed brucellosis experienced EO complications [27]. Numerous studies have documented that EO can be a subsequent manifestation of systemic disease following a prior Brucella infection [2,3,24,25].…”
Section: Discussionsupporting
confidence: 88%
“…However, our findings align with those from Pakistan, where Brucella-related EO was reported in 16.7% (n = 23) of 138 EO cases [26]. Similarly, a study in China revealed that 30.7% of patients with confirmed brucellosis experienced EO complications [27]. Numerous studies have documented that EO can be a subsequent manifestation of systemic disease following a prior Brucella infection [2,3,24,25].…”
Section: Discussionsupporting
confidence: 88%
“… 2 Each species has its optimal host, of which only the first four species can infect humans. 3 Among them, B. melitensis is the most virulent and dominant species associated with human brucellosis in China. 3 , 4 Brucellosis is a disease caused by Brucella with symptoms including long-term fever, hyperhidrosis, arthralgia, fatigue, and pain.…”
Section: Introductionmentioning
confidence: 99%
“… 3 Among them, B. melitensis is the most virulent and dominant species associated with human brucellosis in China. 3 , 4 Brucellosis is a disease caused by Brucella with symptoms including long-term fever, hyperhidrosis, arthralgia, fatigue, and pain. 5 Brucellosis a very common but long-forgotten zoonosis that was repopulated in China since 1995, and the affected areas were mainly localized in northern China such as Inner Mongolia, Shanxi, Heilongjiang, Hebei, Jilin, and Shaanxi.…”
Section: Introductionmentioning
confidence: 99%